Geo-Chicago 2016 : sustainable waste management and remediation : selected papers from sessions of Geo-Chicago 2016, August 14-18, 2016, Chicago, Illinois - Yesiller, Nazli; Zekkos, Dimitrios; Farid, Arvin; De, Anirban; Reddy, Krishna R. (Geotechnical special publication ;, 2016)
Contains 75 peer-reviewed papers on remediation, containment, public policy, and education in geoenvironmental engineering. Topics include: sustainable waste management and remediation; containment rate and transport; electrokinetic remediation; contaminated sediments; remediation methods; solidificaton/stabilization; and public policy and regulations.